2023
DOI: 10.3389/fphar.2023.1090895
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a prognostic model for HCC based on ferroptosis-related lncRNAs expression and its potential to predict the response and irAEs of immunotherapy

Abstract: Background: Ferroptosis is an iron-dependent programmed cell death process, and studies have confirmed that it plays an important regulatory role in the occurrence and development of various malignancies including hepatocellular carcinoma (HCC). In addition, the role of abnormally expressed long non-coding RNAs (lncRNAs) in regulating and driving the occurrence and development of HCC has attracted more and more attention. However, there is still a lack of research on the role of ferroptosis-related lncRNAs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Studies have revealed that plasma level of HULC and NEAT1 are markedly elevated in HCC patients [ 144 , 145 ], serving as significant predictors of HCC tumor growth and metastasis, which hold promise as non-invasive biomarkers for diagnosing hepatoma, and their diagnostic accuracy may be enhanced when combined with AFP [ 145 147 ]. Moreover, several studies have developed HCC prognostic models based on ferroptosis-related lncRNA signatures, aiming to enhance survival prognostication in HCC through tumor classification [ 127 , 148 ]. These ferroptosis-related lncRNAs significantly contribute to the immunosuppressive tumor microenvironment and clinically therapeutic response in HCC, potentially aiding in individualized prognosis determination and treatment planning for HCC patients [ 127 , 148 ].…”
Section: Ferroptosis-related Lncrnas In Hcc Progression and Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have revealed that plasma level of HULC and NEAT1 are markedly elevated in HCC patients [ 144 , 145 ], serving as significant predictors of HCC tumor growth and metastasis, which hold promise as non-invasive biomarkers for diagnosing hepatoma, and their diagnostic accuracy may be enhanced when combined with AFP [ 145 147 ]. Moreover, several studies have developed HCC prognostic models based on ferroptosis-related lncRNA signatures, aiming to enhance survival prognostication in HCC through tumor classification [ 127 , 148 ]. These ferroptosis-related lncRNAs significantly contribute to the immunosuppressive tumor microenvironment and clinically therapeutic response in HCC, potentially aiding in individualized prognosis determination and treatment planning for HCC patients [ 127 , 148 ].…”
Section: Ferroptosis-related Lncrnas In Hcc Progression and Prognosismentioning
confidence: 99%
“…Moreover, several studies have developed HCC prognostic models based on ferroptosis-related lncRNA signatures, aiming to enhance survival prognostication in HCC through tumor classification [ 127 , 148 ]. These ferroptosis-related lncRNAs significantly contribute to the immunosuppressive tumor microenvironment and clinically therapeutic response in HCC, potentially aiding in individualized prognosis determination and treatment planning for HCC patients [ 127 , 148 ]. For example, Wang and his colleagues have established a model based on ferroptosis-related lncRNAs that could accurately predict HCC prognosis, with associations to tumor grade, macrophage and fibroblast infiltration [ 149 ].…”
Section: Ferroptosis-related Lncrnas In Hcc Progression and Prognosismentioning
confidence: 99%
“…With the advancements in bioinformatics technology, several prognostic gene characteristics have been developed (16,17). In the case of HCC, numerous multi-gene signature characteristics, such as the well-known ferroptosis signature (18), m6A signature (19), and others (20), have been discovered to assess patient risk.…”
Section: Introductionmentioning
confidence: 99%